Anatomical and physiological responses of Billbergia zebrina (Bromeliaceae) under different in vitro conditions - Martins, João Paulo Rodrigues (2015)
The thesis was divided in four articles, in which three are related to in vitro propagation and how the microenvironmental conditions play on physiology and anatomy of B. zebrina. The last article is related to anatomical and physiological changes of B. zebrina under copper (Cu) excess stress. For all studies, B. zebrina plants were previously in vitroestablished in MS medium. Plants were transferred to media at concentrations of 0%, 50%, 100%, 150% or 200% of the original salt concentration of MS medium. The media were prepared in two different consistencies, stationary liquid and 6 g L-1 agar. For in vitro rooting studies, the shoots grew in a medium supplemented with different sucrose concentrations. Soluble carbohydrates contents were assessed after the rooting. The in vitro multiplication of B. zebrina shoots is enhanced by using 200% of MS-salts concentration and liquid medium. The use of 15 g L-1 sucrose increased endogenous carbohydrate stocks and induced a good formation of the root systems on in vitro shoots. From these results, a second experiment was designed. B. zebrina side shoots were transferred to culture media containing 0.0, 15.0, 30.0, 45.0 or 60.0 g L-1 sucrose. Two different culture container sealing systems were tested: lids with a filter and a filter covered with PVC. At 45 days in vitro growth, B. zebrina plants were transplanted onto suitable soil mix and evaluated at 80 days growth in greenhouse. At 45 days in vitro and 80 days of acclimatization in the greenhouse, the biomass of plants was evaluated. Anatomical and physiological analysis were also performed on plants grown in vitro. Limited air exchange resulted in plantlets with anatomical and physiological disorders at the end of the in vitro period. The highest growth rate in the greenhouse was observed in plants previously propagated in unlimited gas exchange system and sugar-free medium. An environmental approach was proposed in the last study, in which copper was used. Anatomical and growth analysis were measured. Plants did not show any visible disturb, like necrosis on the leaves and all plants survived. Plants grown under 200 µM Cu showed anatomical changes that can help tolerating this metal, like high stomatal index and thicker cell wall in exodermis. Cu affected the leaf and root anatomy as well as on growth. B. zebrina tolerates high amounts of Cu. From the results it was possible to verify that microenvironmental conditions can change the growth, physiology and anatomy of B. zebrina during in vitro culture. In vitro technique showed a great potential on plant propagation of B. zebrina as well as it also presented an important tool for studies on plant physiology and anatomy.